Calidad de servicio y satisfacción de los comensales del comedor universitario en la Universidad Nacional de la Amazonia Peruana – Iquitos 2024 - Marín Pérez, Stefany Priscila (2024)
The satisfaction of diners in the university dining room of the National University of the Peruvian Amazon plays a fundamental role in the performance of students, since it is closely linked to their satisfaction and well being. The following research work aimed to determine the relationship between quality of service and satisfaction of the diners of the university dining room at the National University of the Peruvian Amazon -Iquitos 2024. The methodology of the present study concerns the type of descriptive, correlational and transversal research. . The population consisted of 300 students and the sample was 169 students. For the purpose of evaluating quality, the questionnaire adapted from the SERVQUAL model and a questionnaire on the satisfaction of diners in the university cafeteria were used as an instrument. To determine the relationship between the study variables, the Spearman Rho Correlation Coefficient statistical test was used, with a confidence level of 0.05. The results on quality show that 74.56% of students perceive the quality of the service as good, 21.89% as average and only 3.55% as bad. Regarding satisfaction, it was found that 64.50% perceived high satisfaction, 31.36% perceived average satisfaction, and only 4.14% perceived low satisfaction. It is concluded that there is a direct relationship between the study variables with a moderate degree of relationship.